2012
DOI: 10.1061/(asce)cc.1943-5614.0000284
|View full text |Cite
|
Sign up to set email alerts
|

Effective Moment of Inertia Prediction of FRP-Reinforced Concrete Beams Based on Experimental Results

Abstract: Concrete beams reinforced with glass-fiber reinforced polymer (GFRP) bars exhibit large deflections in comparison with steel-reinforced concrete beams because of the low modulus of elasticity of GFRP bars. This paper proposes new equations for estimating the effective moment of inertia of FRP-reinforced concrete beams on the basis of the genetic algorithm and experimental results. Genetic algorithm is used to optimize the error function between experimental and analytical responses. In the experimental part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…First, FRP-RC beams exhibit lower serviceability performance owing to the lower modulus of elasticity of FRP bars compared to steel bars [11][12][13]. Secondly, FRP-RC beams are usually designed as over-reinforced because concrete crushing failure is less brittle and less catastrophic compared to FRP rupture failure owing to the rigid and brittle behaviour of FRP bars.…”
Section: Introductionmentioning
confidence: 99%
“…First, FRP-RC beams exhibit lower serviceability performance owing to the lower modulus of elasticity of FRP bars compared to steel bars [11][12][13]. Secondly, FRP-RC beams are usually designed as over-reinforced because concrete crushing failure is less brittle and less catastrophic compared to FRP rupture failure owing to the rigid and brittle behaviour of FRP bars.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Bransonʼ s equation, the equations that were proposed by Mousavi et al (2012) [24], the effective moment of inertia, can be calculated using Equations as follows.…”
Section: Existing Models For Effective Moment Of Inertia Calculationmentioning
confidence: 99%
“…Moreover, Bischoff and Gross [28,29] demonstrated that a sudden loss of stiffness at cracking affected the deflection and post-cracking behaviour. Mousavi et al [30] investigated deflection of GFRP-RC beams, and alleged that the low elastic modulus (E) of GFRP bars causes sudden loss of concrete stiffness. In addition, the bond coefficient and elastic modulus (E) of FRP were the main factors manipulating the GFRP-RC beam behaviour.…”
Section: Introductionmentioning
confidence: 99%